2021
DOI: 10.12688/f1000research.51240.1
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying media sources of information and levels of knowledge about COVID-19: a rapid mini-review of cross-sectional studies in Africa

Abstract: COVID-19 control is highly affected by knowledge levels which are also affected by receipt of information on the disease. Therefore, this review examined knowledge levels and media sources of information findings of the studies on knowledge, attitudes, perceptions, and practices towards COVID-19 done in low- and middle-income countries in Africa to shed light on the interplay of the use of different media platforms and populations’ knowledge about the COVID-19 pandemic and identify shorter- and longer-term pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Although infodemics are often associated with negative impacts, eight reviews reported positive outcomes related to infodemics on social media during a pandemic. 21 , 23 , 24 , 29 33 Social media can be used for crisis communication and management during emerging infectious disease pandemics, regardless of geographical location of the recipient of information. Furthermore, reviews found that dissemination of information on several social media platforms had significantly improved knowledge awareness and compliance to health recommendations among users.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although infodemics are often associated with negative impacts, eight reviews reported positive outcomes related to infodemics on social media during a pandemic. 21 , 23 , 24 , 29 33 Social media can be used for crisis communication and management during emerging infectious disease pandemics, regardless of geographical location of the recipient of information. Furthermore, reviews found that dissemination of information on several social media platforms had significantly improved knowledge awareness and compliance to health recommendations among users.…”
Section: Resultsmentioning
confidence: 99%
“…One systematic review evaluated the knowledge levels and media sources of information about coronavirus disease 2019 (COVID-19) in African countries 29 and found that 40% (4/10) of studies reported that the participants used social media as their source to acquire information about COVID-19. Likewise, traditional communication channels (such as television and radio stations), family members and places of worship were also used to receive information about the disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that challenge, many authors insist on the fact that understanding information is critical to the success of public health interventions and the reduction of health inequalities 25 28 . Currently, health literacy is called to have an even more important role as it is being combined with media literacy to improve understanding of the disease, the associated public health measures and reduce misinformation 13 , 16 , 30 . Understanding information related to COVID-19 and to public health measures is also important for the proper application of public health measures: for example, understanding that COVID-19 is an airborne virus might encourage an individual to wear a mask and to keep distances from others 13 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…20 A systematic review conducted to assess the media sources of information and knowledge levels about COVID-19 revealed that 40% of the population depended on social media as their primary source of information regarding the disease. 21 The increased circulation of misinformation in social media platforms during the accelerated health emergency has led to a cataclysmal infodemic.…”
Section: Discussionmentioning
confidence: 99%